Impact of Islamic Marketing Strategies on Firm Performance: Evidence from Jaiz Bank, Plc. Nigeria - Ismaila Yusuf Mustapha; Abdulazeez Olamide AbdulQuadri (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The global business landscape has recently observed a notable increase in the adoption of specialized marketing strategies tailored to align with cultural, religious, and ethical principles. One prominent example of such a strategy is Islamic marketing, which caters to Muslim consumers' preferences and needs while upholding Islamic finance tenets. This study investigates the impact of Islamic marketing strategies on firm performance, focusing on Jaiz Bank, Nigeria's leading non-interest bank. Using a quantitative approach, this study analyzed secondary data from annual reports over a ten-year period (2012–2021) and apply linear regression to examine the relationship between Islamic marketing practices and key financial metrics: return on assets (ROA), dividend yields, and earnings per share (EPS). Results reveal a statistically significant impact of Islamic marketing on EPS, while its influence on dividend yields is limited, and its effect on ROA is not statistically significant. These findings suggest that while Islamic marketing strategies can enhance certain financial outcomes, they may require refinement or supplementation to drive comprehensive firm performance. This study contributes to the emerging field of Islamic marketing by offering empirical insights into its financial impacts, with implications for strategic development in Islamic financial institutions.